The Role of Human Rights Courts in the Digital Era: Protecting Personal Data and Privacy - Nisa, Zahratun (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
The development of the digital ecosystem in Indonesia has expanded data-based services, but it has also increased incidents of personal data breaches, misuse of information, and privacy violations that threaten the security and dignity of citizens. Studies on data protection in Indonesia have generally focused on regulations and administrative institutions, while the role of the judiciary as an instrument for the protection of human rights in digital data disputes remains limited. This study aims to analyze the position of personal data and privacy as part of human rights, examine the role of the judiciary, and formulate directions for strengthening judicial functions in realizing digital justice in Indonesia. The research employs a library research method with a normative legal approach through the collection, classification, and analysis of primary legal materials, books, and Indonesian-language scientific journals published between 2020 and 2025. The findings reveal four main judicial functions: affirming the constitutional status of personal data, reviewing the legality of state actions, resolving disputes related to data violations, and providing remedies through judicial mechanisms. Therefore, the judiciary plays a concrete role as a guardian of privacy rights, a supervisor of digital accountability, and a pillar of human rights-based digital justice in contemporary Indonesia.